2022
DOI: 10.1093/ehjci/jeac147
|View full text |Cite
|
Sign up to set email alerts
|

A framework of deep learning networks provides expert-level accuracy for the detection and prognostication of pulmonary arterial hypertension

Abstract: Aims To test the hypothesis that deep learning (DL) networks reliably detect pulmonary arterial hypertension (PAH) and provide prognostic information. Methods and results Consecutive patients with PAH, right ventricular (RV) dilation (without PAH), and normal controls were included. An ensemble of deep convolutional networks incorporating echocardiographic views and estimated RV systolic pressure (RVSP) was trained to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…24 Studies by Gerhard-Paul Diller has shown that deep learning can not only accurately diagnose IPAH, but also predict the prognosis of patients. 14 But they need more echocardiographic information to build the model and were investigated in a more restricted patient groups. On the other hand, our ML model not only learned about the spatial features of the left and RVs in PH patients, but also their temporal features, such as the changes in the size of the two chambers during systole and diastole.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…24 Studies by Gerhard-Paul Diller has shown that deep learning can not only accurately diagnose IPAH, but also predict the prognosis of patients. 14 But they need more echocardiographic information to build the model and were investigated in a more restricted patient groups. On the other hand, our ML model not only learned about the spatial features of the left and RVs in PH patients, but also their temporal features, such as the changes in the size of the two chambers during systole and diastole.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have suggested an improvement in diagnostic performance using ML models, such as ML algorithms based on Logit Boost can better identify precapillary PH and post‐capillary PH 24 . Studies by Gerhard‐Paul Diller has shown that deep learning can not only accurately diagnose IPAH, but also predict the prognosis of patients 14 . But they need more echocardiographic information to build the model and were investigated in a more restricted patient groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Artificial intelligence could have many applications in CHD, such as improving detection and diagnosis, prediction of prognosis, and guiding therapy. 73 , 74 Other potential applications include prediction of the effect of drugs and/or interventions 75 , 76 and incorporation of “soft” outcomes such as exercise capacity and quality of life into the decision-making process. The clinical applications using AI on CMPs and congenital heart diseases are summarized in Table 5 .…”
Section: Introductionmentioning
confidence: 99%